Relations between White Matter Maturation and Reaction Time in Childhood. (29th October 2013) - Scantlebury, Nadia; Cunningham, Todd; Dockstader, Colleen; Laughlin, Suzanne; Gaetz, William; Rockel, Conrad; Dickson, Jolynn; Mabbott, Donald
Abstract White matter matures with age and is important for the efficient transmission of neuronal signals. Consequently, white matter growth may underlie the development of cognitive processes important for learning, including the speed of information processing. To dissect the relationship between white matter structure and information processing speed, we administered a reaction time task (finger abduction in response to visual cue) to 27 typically developing, right-handed children aged 4 to 13. Magnetoencephalography and Diffusion Tensor Imaging were used to delineate white matter connections implicated in visual-motor information processing. Fractional anisotropy (FA) and radial diffusivity (RD) of the optic radiation in the left hemisphere, and FA and mean diffusivity (MD) of the optic radiation in the right hemisphere changed significantly with age. MD and RD decreased with age in the right inferior fronto-occipital fasciculus, and bilaterally in the cortico-spinal tracts. No age-related changes were evident in the inferior longitudinal fasciculus. FA of the cortico-spinal tract in the left hemisphere and MD of the inferior fronto-occipital fasciculus of the right hemisphere contributed uniquely beyond the effect of age in accounting for reaction time performance of the right hand. Our findings support the role of white matter maturation in the development of information processing speed. (JINS, 2013, 19, 1–14)